The environmental and health impact of air and soil pollution resulting from sanitary landfill sites in Thi Qar Governorate - Muhaisen, Ass.Prof PhD Abbas Zghair (Thi Qar Arts Journal, 2023)
The spatial monitoring of sanitary landfill sites in Thi Qar Governorate, with five administrative districts, under the environmental determinants of air and soil pollution, varied concentrations of carbon monoxide gas (Co) spatially and temporally in landfill sites, as it recorded the highest concentration in winter (31.64 PPm) As for formaldehyde gas (HCHO) (PP 3.28) As for spatially, the landfill site in Nasiriyah recorded the highest concentration (40.6 ppm, 5.8 ppm) of gas (Co, HCHo) respectively, due to the amount and quality of waste that is thrown into the environment and exposed to random burning daily and when comparing the results of field monitoring of air pollution with carbon monoxide gas with the environmental determinant and health impact, it becomes clear that a number of landfill sites exceeded the environmental determinant for an hour, including landfill (Nasiriyah summer and winter, while all sites and their results fixed in the spatial average determinant The environmental and the amount of (PPM 35) hours, and the health effects of gas (Co) indicate that the most severe of them were recorded in winter at the landfill site in Nasiriyah within severe pollution and caused (difficulty in speaking and susceptibility to collapse), and other landfill sites were recorded (within severe pollution) which causes (weakness in muscles and blindness and feeling dizzy), and it appears from the health effect of gas (HCHO), that the landfill site in Nasiriyah is within (severe pollution) that causes (burning of the eye) and the respiratory system as well as tearing and difficulty breathing while all other landfill sites in the province recorded (medium pollution) As for soil pollution with heavy elements, the highest concentration of iron element (Fe) was recorded at the landfill site in Nasiriyah by (252 micrograms / m3), and ranked second, the landfill site in Shatrah (182 mg / m3), and the concentration of copper came at the landfill site in Shatrah by (40 micrograms / m3) Then ranked second, the landfill site in Nasiriyah by (34 micrograms / m3), and the highest concentration of lead was recorded at the landfill site in Nasiriyah by (14.5) and it also appears that all landfill sites exceeded the environmental determinant of (5) and therefore this element causes irritation in the membranes of the bronchi of the respiratory system, as for cadmium, the landfill site in Nasiriyah occupied the highest concentration (0.182) and ranked second, the landfill site in Rifa’i with a concentration (0.163), all landfill sites exceeded the environmental determinant of (0.01). Received 6/7/2023, Accepted 5/8/2023 Published 30/9/2023